2020
DOI: 10.1037/edu0000384
|View full text |Cite
|
Sign up to set email alerts
|

Improving fraction understanding in sixth graders with mathematics difficulties: Effects of a number line approach combined with cognitive learning strategies.

Abstract: The effectiveness of an experimental middle school fraction intervention was evaluated. The intervention was centered on the number line and incorporated key principles from the science of learning. Sixth graders (N = 51) who struggled with fraction concepts were randomly assigned at the student level to the experimental intervention (n = 28) or to a business-as-usual control who received their school’s intervention (n = 23). The experimental intervention occurred over 6 weeks (27 lessons). Fraction number lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 98 publications
(140 reference statements)
2
50
0
1
Order By: Relevance
“…Similar to previous studies applying NLE training to children, we expected the training to improve participants' conceptual knowledge of fraction magnitude on a behavioral level [20,21]. In particular, we expected significant improvements in NLE performance over the fiveday training sessions.…”
Section: The Present Studysupporting
confidence: 64%
See 2 more Smart Citations
“…Similar to previous studies applying NLE training to children, we expected the training to improve participants' conceptual knowledge of fraction magnitude on a behavioral level [20,21]. In particular, we expected significant improvements in NLE performance over the fiveday training sessions.…”
Section: The Present Studysupporting
confidence: 64%
“…The aim of the present study was to investigate potential neuro-functional changes of brain activation in adult participants through a five-day consecutive NLE training on fraction magnitude. While there already exist a number of studies indicating the effectiveness of NLE training on the behavioral level [20][21][22]60] and some few studies investigating the neural correlates of fraction and proportion processing [41,42,44,45], little is still known about the neural correlates of fraction learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, math-specific language is a necessary skill that supports connecting fraction symbols and fraction representations. Students in grades 4 and 6 were compared because previous research has shown that this is a critical time period for students to consolidate their fraction knowledge (Barbieri et al, 2019;Hansen et al, 2017;Jordan et al, 2017). In addition, the students in the present research were first taught fraction symbols in grade 4; by grade 6, students were expected to have had a reasonable amount of practice using fraction symbols and thus their fraction knowledge should be more advanced.…”
Section: The Current Researchmentioning
confidence: 99%
“…Yet, if prior knowledge or the capabilities and motivation to integrate new knowledge into existing knowledge structures are lacking, these cognitively activating instructional methods are unlikely to produce significant knowledge gains [ 22 ]. Instruction involving representational gestures, physical movement, and systematic feedback, for instance, has proven effective in sixth graders with mathematics difficulties [ 29 ]. Students with non-beneficial cognitive potential—i.e., with low content-specific and strategic prior knowledge, motivation, or less developed reasoning abilities—seem to particularly profit from tablet-based mathematics instruction featuring animations, adaptive tasks, and guidance during practice [ 22 , 30 ].…”
Section: Introductionmentioning
confidence: 99%